RESILIENSI BUDAYA ORGANISASI BERBASIS LOCAL WISDOM: MITIGASI DISRUPSI GLOBAL PADA SATUAN PENDIDIKAN DASAR DI KAWASAN PARIWISATA INTERNASIONAL - Gede Agung, Anak Agung; Chindytia; Ni Komang Indah Permata Dewi; Ni Komang Ayu Trijayanti; Emilia Sinta Tambunan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigated the resilience mechanisms of primary schools in the international tourism area of Jalan Pantai Berawa, Bali, in mitigating global cultural disruption. The primary issue concerned the vulnerability of student character to permissive external values and the gap between school cultural practices and administrative formality. This research aimed to formulate a resilient student management model through the integration of School-Based Management (SBM) and local wisdom. Employing a qualitative descriptive case study approach, data were collected through observation, interviews, and document studies at SD No. 3 Tibubeneng. The results show that the habituation of the 5S Culture effectively functions as a cultural filter that strengthens students' character immunity. However, a weakness in legality is found due to the absence of written disciplinary documents. This study concludes by recommending the "Cultural-Administrative Resilience Model" as a strategic solution through the synchronization of local values into formal school regulations to ensure institutional accountability and sustainability. Keywords: School-Based Management, Organizational Resilience, Local Wisdom, Cultural Disruption, Student Management.